2021
DOI: 10.3389/fphys.2021.696256
|View full text |Cite
|
Sign up to set email alerts
|

Selenoproteins Protect Against Avian Liver Necrosis by Metabolizing Peroxides and Regulating Receptor Interacting Serine Threonine Kinase 1/Receptor Interacting Serine Threonine Kinase 3/Mixed Lineage Kinase Domain-Like and Mitogen-Activated Protein Kinase Signaling

Abstract: Liver necroptosis of chicks is induced by selenium (Se)/vitamin E (VE) deficiencies and may be associated with oxidative cell damage. To reveal the underlying mechanisms of liver necrosis, a pool of the corn–soy basal diet (10 μg Se/kg; no VE added), a basal diet plus all-rac-α-tocopheryl acetate (50 mg/kg), Se (sodium selenite at 0.3 mg/kg), or both of these nutrients were provided to day-old broiler chicks (n = 40/group) for 6 weeks. High incidences of liver necrosis (30%) of chicks were induced by –SE–VE, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…In addition, GPX4 mediates the suppression of pyroptosis and ferroptosis in acute pancreatitis [ 22 ]. Although GPX4 is often lowly expressed and is resistant to Se deficiency in mammalian tissues [ 23 ], it is abundantly expressed in chicken tissues and readily affected by Se deficiency [ [24] , [25] , [26] ]. Because of its unique expression pattern in chickens and its potent role in cell death [ [27] , [28] , [29] ], GPX4 might serve as a key selenoprotein involved in the pathogenesis of NPA.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, GPX4 mediates the suppression of pyroptosis and ferroptosis in acute pancreatitis [ 22 ]. Although GPX4 is often lowly expressed and is resistant to Se deficiency in mammalian tissues [ 23 ], it is abundantly expressed in chicken tissues and readily affected by Se deficiency [ [24] , [25] , [26] ]. Because of its unique expression pattern in chickens and its potent role in cell death [ [27] , [28] , [29] ], GPX4 might serve as a key selenoprotein involved in the pathogenesis of NPA.…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation is that pregnant rats may have an adaptive mechanism to limit maternal serine utilization and ensure adequate supply to the fetus when the supply of serine is insufficient (caused by either insufficient exogenous serine or impaired endogenous serine synthesis) ( 27 , 29 ). This was supported by a decrease in selenoprotein (DIO1/2) synthesis in the maternal organs and tissues but an increase in plasma selenoproteins (SELENOP and GPx3) concentration for transport to the fetus ( 30 ). Furthermore, low expression of liver DIO1/2 did not led to changes in plasma T4 and T3 in pregnant rats either on a low serine diet or given NCT503.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, studies have found that GPX4 is not only an inhibitor of ferroptosis, but also plays an important role in inhibiting necroptosis ( Canli et al, 2016 ). At the same time, some studies have found that the redox homeostasis of cells also plays an important role in necroptosis ( Florean et al, 2019 ; Zhang Y et al, 2020 ; Li et al, 2021 ). Decreased GSH and SOD levels lead to increased oxidative stress in cells, which can induce necroptosis in cells ( Xie et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%